2009
DOI: 10.1111/j.1600-0846.2009.00365.x
|View full text |Cite
|
Sign up to set email alerts
|

Skin from various ethnic origins and aging: an in vivo cross‐sectional multimodality imaging study

Abstract: Background: Ethnic differences in skin structural features have not been thoroughly investigated, and the few reported studies are contradictory. Thus, we have carried out a set of in vivo measurements on the skin of about 400 volunteers from various ethnic origins living in the same environment. Methods: Female subjects were distributed into four ethnic groups: African Americans, Mexicans, Caucasians, and Chinese. Inter‐ and intra‐ethnic skin structural differences, according to age and anatomic site, were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
63
1
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(72 citation statements)
references
References 42 publications
5
63
1
3
Order By: Relevance
“…However, unlike other investigations [19, 20], epidermal thickness significantly differed among the three ethnic groups with the following decreasing order: Blacks > Asians > Caucasians. Querleux et al [19] measured the skin thickness in different ethnic groups using ultrasound and reported that the skin (epidermis + dermis) and subepidermal nonechogenic band representing dermis were thicker on the cheek in all groups comparing to the arm. When the measurements of this study are evaluated, a thicker epidermal layer on the cheek is detectable as compared to the epidermal thickness of the volar arm [19].…”
Section: Discussioncontrasting
confidence: 44%
See 3 more Smart Citations
“…However, unlike other investigations [19, 20], epidermal thickness significantly differed among the three ethnic groups with the following decreasing order: Blacks > Asians > Caucasians. Querleux et al [19] measured the skin thickness in different ethnic groups using ultrasound and reported that the skin (epidermis + dermis) and subepidermal nonechogenic band representing dermis were thicker on the cheek in all groups comparing to the arm. When the measurements of this study are evaluated, a thicker epidermal layer on the cheek is detectable as compared to the epidermal thickness of the volar arm [19].…”
Section: Discussioncontrasting
confidence: 44%
“…Noninvasive in vivo imaging methods such as OCT and RCM provide real time, painless and repeated monitoring and quantification of the tissues. Few studies have been performed regarding the assessment of skin morphology in different ethnic groups with noninvasive imaging methods [19, 20]. However, to the best of our knowledge, interethnic comparison of noninvasive treatment follow-up has not been performed to date.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…OCT is a non-invasive interferometric technique that is capable of resolving skin architecture, in vivo and in real time, at micrometer scale and up to a depth of 1-2 mm, solely based on local optical backscatter (31,32). The principles of OCT are often likened to ultrasound, and the technology has been used to characterise structural and biomechanical features of both 'normal' and diseased human skin (33)(34)(35)(36)(37)(38)(39). Whilst OCT is establishing itself as a routine imaging method in ophthalmology, the evaluation of skin is at a more developmental stage.…”
Section: Introductionmentioning
confidence: 99%